Study of Ectopic Pregnancy at Tertiary Care Hospital in Province 1 of Nepal - Ghimire, Sita Pokhrel (Journal of Nepal Health Research Council, 2021)
Background: Ectopic pregnancy can be managed expectantly, medically or surgically. Laparoscopic surgery is considered gold standard. The aim of this study was to find incidence, risk factors, clinical presentation and mode of management of ectopic pregnancy.Methods: Prospective descriptive study was conducted at Nobel Medical College and Teaching Hospital, Biratnagar. All the cases of diagnosed ectopic pregnancy were enrolled in the study. All the relevant data of the patients were recorded in pre-designed Performa. The collected data were entered in MS Excel and exported into SPSS 21 version for statistical analysis.Results: The incidence of ectopic pregnancy was 0.8%. Most of the patients (35 ;( 58.3%) belonged to 20-30 age group. The classic triad of pain abdomen, amenorrhea and per vaginal bleeding was present in 41 (68.3%) cases. The most common risk factor associated was PID (39 ;-( 65%) followed by abortion 98 ;-( 13.3%). USG findings were suggestive of ruptured ectopic pregnancy, which was seen in 52(86.7%) cases and. 93.3% of the cases were managed surgically. The most common site of ectopic pregnancy was found to be ampulla 35(58.3%) followed by isthmus 11(18.3%). There was no mortality.Conclusions: Pelvic inflammatory disease was the commonest risk factor, laparotomy was the commonest modality of surgical management and ampulla was the commonest site of ectopic pregnancy. Early diagnosis, referral and treatment in the tertiary care center prevents morbidity and mortality related to ectopic pregnancy.Keywords: Ectopic pregnancy; methotrexate; ultrasonography